EFFECTS OF MID-HOLOCENE RIVER RUNOFF ON THE ARCTIC OCEAN/SEA-ICE SYSTEM: A NUMERICAL MODEL STUDY - Prange M.; Lohmann G. (My University, 2003)
Recent geological studies have revealed that the freshwater input to the Arctic Ocean was highly variable during the Holocene. In the present study, the in uence of mid-Holocene river runoff on large-scale Arctic ocean/sea-ice dynamics is examined using a general circulation model. A palaeohydrological forcing for the time interval around 6 ka BP (14 C timescale) is constructed by compiling data from the available literature. Keeping all other forcing elds and bottom topography of the ocean model at present-day values, the effect of a changed freshwater input to the Arctic Ocean is isolated. The model shows that freshwater supply is vitally important for the polar oceanic circulation. In particular, a close connection between Siberian river runoff and the path of the Transpolar Drift (TPD) is found. Consistent with palaeoceanographic ndings of driftwood delivery to the Canadian Arctic Archipelago and Baff n Bay, the model results suggest that enhanced freshwater discharge during the mid-Holocene caused an eastward shift of the TPD with strengthened out ow through Fram Strait.
Keywords: Ocean/sea-ice modelling; Arctic river runoff; Arctic palaeoceanography; Transpolar Drift; Holocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен